Terminological Problems in Academic Writing : A Study of Texts Written by University Students - Katajamäki, Heli (VAKKI ry, 2020)
This study focuses on terminological problems, which students encounter in academic writing. In the academic writing course Academic Writing in Finnish (5 ECTS), students perform an argumentation analysis, which is reported by writing a short academic text, called a mini-thesis. For the argumentation analysis, students analyse a Master’s thesis written by some other student based on the theoretical background given during the course. In this paper I will describe terminological problems encountered by ten students in this task. The aim is to illustrate that students may have a conceptual understanding of the concepts (argument, main claim, claim, reason, background assumption) required for the assignment but still resort to using term-like words vaguely, ambiguously or sometimes even wrongly. The results of a genre and discourse analysis show that this is the case in some respects. Terminological problems illustrate how the terminological chain from the sources of the assignment to the assignment and further to the mini-thesis might be broken, and as a consequence, the intelligibility of the mini-thesis can be put at risk. However, some students use the term-like words consistently and even show some development if compared with the terms given in the theoretical background. The results may have pedagogical use in shedding light on how consistent use of terms strengthens intelligibility.
Keywords: genre chain; mini-thesis; terminological problems; term-like words; academic writing